Pengaruh Persepsi Nilai Terhadap Niat Beli Pada Makanan Organik - Franky Anggreiawan; Jul Aidil Fadli (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
In the era of globalization, more and more new market segments are concerned about the environment, and the demand for organic food is increasing as well. This market segment, called green consument, incorporates organic foods into their daily diet and encourages changes in their attitudes, beliefs, motivations, and values towards the consumption of certain foods. The purpose of this study is to determine the relationship between the perceived value dimension (functional, emotional, social, economic value) to the intention to buy organic food in the Bekasi City Region. The method in this study uses a quantitative approach. The study was conducted on 105 general respondents who intended to buy organic food and were domiciled in Bekasi City. The sampling technique in this study is purposive sampling-judgement sampling and convenience with online sampling. The instrument used was in the form of a questionnaire that was distributed to respondents online. The data that has been collected, is then processed using SPSS 25 software by the method of multiple linear regression analysis. Based on the study, it was found that there was a significant relationship between the functional value variable (X1), the emotional value variable (X2), the economic value variable (X3) and the social value variable (X4) to the purchase intention variable (Y) simultaneously by 26.4%. Partially, there are variables that are not significantly related to the purchase value variable, namely the functional value variable (X1) and the social value variable (X4).